Biometric and morphological features on magnetic resonance imaging of fetal bladder in lower urinary tract obstruction: new perspectives for fetal cystoscopy. (1st July 2020) - Vinit, N.; Grevent, D.; Millischer‐Bellaiche, A.‐E.; Pandya, V. M.; Sonigo, P.; Delmonte, A.; Sarnacki, S.; Aigrain, Y.; Boddaert, N.; Bessières, B.; Benchimol, G.; Salomon, L. J.; et al.
ABSTRACT: Objectives: Incompatibility between currently available fetoscopes and the anatomical constraints of the distended fetal bladder, with the resulting curvature around the bladder neck, account for most technical difficulties during fetal cystoscopy in lower urinary tract obstruction (LUTO). The aim of this anatomical study was to assess by magnetic resonance imaging (MRI) the variation in three bladder angles (bladder‐neck angle (BNA), vesicourethral angle (VUA) and angle between bladder dome and posterior urethra (DUA)), according to gestational age (GA), bladder volume and the presence of LUTO. Methods: From our fetal medicine database, we retrieved for review 46 MRI examinations of male fetuses between 2015 and 2019, including 17 with LUTO, examined at a mean GA of 28.1 (range, 17.3–35.0) weeks and 29 age‐matched controls, examined at 29.9 (range, 21.9–35.0) weeks. We measured bladder volume, bladder‐wall thickness and the three bladder angles, and used the Mann–Whitney U ‐test to compare values between groups. Variations according to GA and bladder volume were determined using analysis of variance (ANOVA). A reliability study was performed using the Bland–Altman method and Lin's correlation coefficient was calculated. Results: Both bladder volume and bladder‐wall thickness were significantly greater in the LUTO group ( P  < 0.01). BNA was significantly larger in LUTO compared with control fetuses: the mean (range) was 127.1° (101.6–161.6°) vs 111.2° (88.5–157.3°) ( P  < 0.01). DUA averaged 117° and showed no difference between the groups ( P  = 0.92). No statistical comparison was performed on VUA since this was not measurable in most control fetuses. ANOVA showed no variation of any angle with bladder volume in both LUTO fetuses and control fetuses. BNA in LUTO fetuses was the only angle to vary with GA, being larger after, compared with at or before, 25 weeks ( P  = 0.04). The reliability study showed an acceptable bias for both intra‐ and interobserver reproducibility for all three angles. Conclusion: The findings that BNA is increased by approximately 15° in fetuses with LUTO and DUA averages 117° could aid in development of a customized fetal cystoscope and help to overcome the current technical challenges of fetal cystoscopy. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.